Happiness Behind The Threat of Disaster: Women in The South Merapi Slope - Hastuti, Hastuti; Widyastuti, Mawanti (KARSA Journal of Social and Islamic Culture, 2018)
The study was conducted with the aim of studying the happiness of women in the slopes of south Merapi in the threat of Merapi disaster. Descriptive research, the theme of geography of human environment interaction with the subject of research of women who live and have socio-economic activities in the District Cangkringan.Â  Population are women married living in the study area. Samples were taken purposively as many as 33 respondents. Research variables socio-economic and female demographics and characteristics of happiness and threat of disaster. Quantitative descriptive data analysis used frequency tables to analyze sociodemograph, happiness women and threat of disaster. Analysis of qualitative data in reduction, presentation and verification. The results showed that women in South Merapi Slope who have socio-economic activities in Cangkringan sub-district understand that their residence area is vulnerable to disaster threat. Merapi disaster can threaten the women of the slopes of south Merapi every time but they believe, that Merapi remains friendly with the people on the slopes. The result of eruptions in the form of hot lava and rain lava, will be a blessing source of income and make their territory remains fertile so that their farm has a good prospect. Merapi has been a blessing not as a disaster, so living in harmony with Merapi can support the happiness of women in the slopes of south Merapi.